ANALYZE ECONOMIC FUNDAMENTALS IN IMTAQ COUNTRIES (INDONESIA, MALAYSIA, TURKEY, ARAB SAUDI AND QATAR) - Ishak, Nadiah; Hasanah, Uswatun (International Proceeding of Law and Economic, 2020)
The study aims to analyse the variable contributions of the variable interaction of financial inclusion policy with monetary policy in the stability of economic growth. Where financial variables inclusion (savings and Non Performance Loan). Then monetary policy (amount of money supply, exchange rate and inflation. This research uses secondary data or time series that is from 1999 to 2018 year. The data analysis model in this study is a Vector Autoregression (VAR) model seen from sharpened with Impulse Response Function (IRF) analysis and Forecast Error Variance Decomposition (FEVD) and ARDL Panel. Analysis result of IRF known that the stability of the response of the entire variable is formed in the period 9 or the medium and long term, where the other variable response to the change of one variable shows different variations of both the positive response to Negative or otherwise, and there are variables that Responya remain positive or remain negative from short to long term. The results of FEVD analysis showed for the savings variables in the long and longer term recommended by the savings itself and the GDP. The NPL variable in the short and long term is recommended by the NPL itself and its savings, while the medium term is influenced by the amount of money supply. Then for JUB variables in the short-term medium and length of JUB are influenced by the NPL. The exchange rate variable is influenced by the NPL in short and medium term. Inflation in the medium and long short term is influenced by the amount of money supply while GDP in the short, medium and long term is influenced by the NPL. Then the ARDL Panel results show countries that are capable of leading indicators for the stability of economic growth are Indonesia, Malaysia and Turkey, this is due to all variables or indicators in the study (saving, NPL, Amount of money supply, exchange rate, and inflation) the country has significant effect on economic growth, while in Saudi Arabia and Qatar only exchange rates that have no effect on economic growth, other variables are savings, NPL, total Money supply, and inflation has an effect on economic growth in the countries of Saudi Arabia and Qatar